ROLE OF RESEARCH IN MANAGEMENT EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the pivotal role of research activities in shaping both student experiences and faculty perceptions within academic institutions. Through a comprehensive survey involving faculty members and students, the study investigates the impact of research on diverse facets, ranging from critical thinking and problem-solving skills to career competitiveness and holistic student development. Findings indicate a strong consensus among faculty members and students regarding the instrumental nature of research in enhancing academic experiences, fostering deeper engagement, and shaping students' future career prospects. The alignment in perceptions emphasizes the need for a more integrated approach to incorporate research into educational frameworks, with implications for curriculum design, faculty development, and institutional support.